รูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียน ของโรงเรียนขยายโอกาสขนาดเล็ก - (Wirat Ketauang), วิรัตน์ เกตุเรือง; (Sukanya Chaemchoy), สุกัญญา แช่มช้อย; (Chalong Chatrupracheewin), ฉลอง ชาตรูประชีวิน (Journal of Education and Innovation, 2017)
การวิจัยครั้งนี้มีจุดมุ่งหมายหลักเพื่อพัฒนารูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษ เพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็ก จุดมุ่งหมายเฉพาะและวิธีการวิจัยดำเนินการ 3 ขั้นตอน 1) ศึกษาสภาพและแนวทางในการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็ก โดยวิธีการศึกษาเอกสาร สนทนากลุ่มผู้บริหาร ครูผู้สอนภาษาอังกฤษ และสัมภาษณ์ผู้ทรงคุณวุฒิ 2) สร้างรูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็กโดยวิธีสนทนากลุ่มผู้ทรงคุณวุฒิ และ 3) ประเมินรูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็กโดยใช้แบบสอบถามกับกลุ่มตัวอย่างผู้บริหารสถานศึกษาและครูผู้สอนภาษาอังกฤษในโรงเรียนขยายโอกาสขนาดเล็กในพื้นที่ภาคเหนือ ภาคกลาง ภาคตะวันออกเฉียงเหนือ และภาคใต้ ผลการวิจัย พบว่า 1. สภาพและแนวทางในการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็กจำแนกเป็น 5 ด้าน ได้แก่ 1) ด้านการใช้หลักสูตร 2) ด้านการจัดการเรียนการสอน 3) ด้านประสิทธิภาพครูผู้สอน 4) ด้านสื่อเทคโนโลยีสารสนเทศและการสื่อสาร 5) ด้านการวัดและประเมินผล 2. รูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็กประกอบด้วย 3 องค์ประกอบ ได้แก่ องค์ประกอบที่ 1 การบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสาร องค์ประกอบที่ 2 การจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสาร องค์ประกอบที่ 3 คุณภาพผู้เรียน และปัจจัยที่เป็นเงื่อนไขของความสำเร็จ ได้แก่ 1) การสร้างความตระหนักแก่ผู้บริหาร ครู และบุคลากรทางการศึกษาให้เห็นถึงความสำคัญของการใช้ภาษาอังกฤษเพื่อการสื่อสาร 2) การส่งเสริมให้ผู้บริหาร ครู และบุคลากรทางการศึกษาเกิดการพัฒนาความรู้และทักษะในการใช้ภาษาอังกฤษเพื่อการสื่อสาร 3. ประเมินรูปแบบการบริหารการจัดการเรียนรู้ภาษาอังกฤษเพื่อการสื่อสารสำหรับนักเรียนของโรงเรียนขยายโอกาสขนาดเล็ก พบว่าทั้ง 3 องค์ประกอบ และปัจจัยที่เป็นเงื่อนไขของความสำเร็จ มีความเป็นไปได้และความเป็นประโยชน์อยู่ในระดับมากทุกรายการ LEARNING MANAGEMENT MODEL OF ENGLISH COMMUNICATION FOR STUDENTS IN SMALL - SIZED OPPORTUNITY EXPANSION SCHOOLS This research aimed to develop learning management model of English communication for the students in the small-sized opportunity Expansion Schools. The specific purpose and research procedures were divided into 3 steps; 1) To study the status and concept of developing the learning management model of English communication for students in small-sized opportunity expansion schools by literature review and analysis, the group discussion of small-sized school administrators and teacher and the interview 12 experts. 2) To draft the learning management model of English communication by the focus group discussion of 10 experts. 3) To evaluate the learning management model of English communication by using a survey questionnaire to the sample of selected small-sized school administrators and teachers in the Northern Central, North-east and Southern provinces. The findings of the research were as follow: 1. The study and concepts learning management Model of English Communication for the students in small-sized opportunity expansion schools consisted of 5aspects as 1) curriculum implementation 2) learning management 3) teachers efficiency 4) Information and communication Technology, and 5) assessment and evaluation. 2. The proposed learning Management model of English communication for the students in the small-sized opportunity expansion schools consists of 3 components as 1) the administrative process, 2) the learning and teaching management process, and 3) the students quality. As for key factors for success, they were 1) awareness of the school administrators and teachers to the importance of English communication, and 2) the encouragement of the school administrators and teachers to develop their English communication. The encouragement program for executives, teachers and academic personnels to develop English communication knowledge and skills. 3. The feasibility and the usability of the model were rated at high levels in all aspects.